Competing priorities in treatment decision-making: a US national survey of individuals with depression and clinicians who treat depression. Issue 1 (8th January 2016) - Barr, Paul J; Forcino, Rachel C; Mishra, Manish; Blitzer, Rachel; Elwyn, Glyn
Abstract : Objective: To identify information priorities for consumers and clinicians making depression treatment decisions and assess shared decision-making (SDM) in routine depression care. Design: 20 questions related to common features of depression treatments were provided. Participants were initially asked to select which features were important, and in a second stage they were asked to rank their top 5 'important features' in order of importance. Clinicians were asked to provide rankings according to both consumer and clinician perspectives. Consumers completed CollaboRATE, a measure of SDM. Multiple logistic regression analysis identified consumer characteristics associated with CollaboRATE scores. Setting: Online cross-sectional surveys fielded in September to December 2014. Participants: We administered surveys to convenience samples of US adults with depression and clinicians who treat depression. Consumer sampling was targeted to reflect age, gender and educational attainment of adults with depression in the USA. Primary outcome measures: Information priority rankings; CollaboRATE, a 3-item consumer-reported measure of SDM. Results: 972 consumers and 244 clinicians completed the surveys. The highest ranked question for both consumers and clinicians was 'Will the treatment work?' Clinicians were aware of consumers' priorities, yet did not always prioritise that information themselves, particularly insurance coverage and cost of treatment. Only 18% of consumers reported high levels of SDM. Working with a psychiatrist (OR 1.87; 95% CI 1.07 to 3.26) and female gender (OR 2.04; 95% CI 1.25 to 3.34) were associated with top CollaboRATE scores. Conclusions: While clinicians know what information is important to consumers making depression treatment decisions, they do not always address these concerns. This mismatch, coupled with low SDM, adversely affects the quality of depression care. Development of a decision support intervention based on our findings can improve levels of SDM and provide clinicians and consumers with a tool to address the existing misalignment in information priorities.